2006
DOI: 10.1021/ct600236q
|View full text |Cite
|
Sign up to set email alerts
|

Using Molecular Dynamics Simulations To Provide New Insights into Protein Structure on the Nanosecond Timescale:  Comparison with Experimental Data and Biological Inferences for the Hyaluronan-Binding Link Module of TSG-6

Abstract: Link module domains play an essential role in extracellular matrix assembly and remodeling by binding to the flexible glycosaminoglycan hyaluronan. A high-resolution NMR-structure of the Link module from the protein product of tumor necrosis factor-stimulated gene-6 (Link_TSG6) has been determined, but a fuller appreciation of protein dynamics may be necessary to understand its hyaluronan-binding. Therefore, we have performed a 0.25 μs MD simulation, starting from the lowest-energy NMR-derived solution structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
(171 reference statements)
3
5
0
Order By: Relevance
“…In order to identify small-scale conformational changes and novel allosteric binding sites the model was subjected to constant temperature MD simulations over 80 ns. While simulations of this time scale are too short to reveal large conformational changes or even protein folding events, it was shown that this time scale is sufficient to explore the conformation of loops and side-chains in agreement with experimental data (Almond et al, 2007;Nederveen and Bonvin, 2005). Our results reveal the molecular details of ATP and peptide substrate ligand binding, the role of the activation loop and conformational changes.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In order to identify small-scale conformational changes and novel allosteric binding sites the model was subjected to constant temperature MD simulations over 80 ns. While simulations of this time scale are too short to reveal large conformational changes or even protein folding events, it was shown that this time scale is sufficient to explore the conformation of loops and side-chains in agreement with experimental data (Almond et al, 2007;Nederveen and Bonvin, 2005). Our results reveal the molecular details of ATP and peptide substrate ligand binding, the role of the activation loop and conformational changes.…”
Section: Introductionsupporting
confidence: 78%
“…The apo-form showed significant structural changes throughout, which would be expected as the protein structure was modelled with the ATP cofactor bound. It should be noted that the simulation time of 80 ns limits the conformational changes to small scale motions in the vicinity of the starting structure, which nevertheless allow the exploration of side-chain movements and loop flexibility that is in agreement with NMR experiments (Almond et al, 2007) and may critically influence ligand binding.…”
Section: Conformational Dynamics Of Ikk-bmentioning
confidence: 68%
“…Conversely, our studies showed that a change in the ionization state of the Link TSG6 residue His 45 is largely responsible for the gain in HA affinity between pH 3.5 and 6; His 45 (equivalent to His 80 in full-length TSG-6) lies adjacent to the HA-binding site and in close proximity to the β4-β5 loop that undergoes a conformational change on association with HA. Another recent development in our investigation of the Link TSG6/HA interaction has come from the use of Molecular Dynamics simulations, allowing insights into the structure of this protein on a nanosecond timescale [9]. The data obtained supported our previous conclusion of an induced-fit mechanism for HA binding TSG-6 (with Link and CUB modules indicated by L and C respectively) reacts with IαI to form covalent TSG-6·HC complexes.…”
Section: Introductionsupporting
confidence: 73%
“…48 Correlation times, τ c , were extracted following the procedure described by Farrow et al 49 Comparisons of the T 1 , T 2 and heteronuclear NOE data for Link_TSG6 with molecular dynamics simulations of the free protein have been documented previously. 50 Crystallography Crystals were grown using the sitting-drop method. A 2.5 μl drop formed from equal amounts of protein solution (7 mg/ml solution in approximately 25 mM Tris-HCl, 75 mM NaCl) and well solution was equilibrated against 1.0 ml well solution (2 M ammonium sulphate, 2% (v/v) PEG 400, 0.1 M sodium Hepes (pH 7.5)).…”
Section: Methodsmentioning
confidence: 99%